2018
DOI: 10.1161/jaha.118.008911
|View full text |Cite
|
Sign up to set email alerts
|

Association of “Elevated Blood Pressure” and “Stage 1 Hypertension” With Cardiovascular Mortality Among an Asian Population

Abstract: BackgroundThe new American College of Cardiology/American Heart Association high blood pressure (BP) guidelines in the United States have lowered definition of hypertension by defining normal as systolic/diastolic BP <120/80 mm Hg; elevated BP as systolic between 120 and 129 mm Hg and diastolic <80 mm Hg; and stage 1 hypertension as systolic between 130 and 139 mm Hg or diastolic between 80 and 89 mm Hg.Methods and ResultsWe investigated the association between the new hypertension definition and cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…The Singapore Chinese Health Study that included 30 636 participants revealed that neither elevated BP nor stage 1 AH was associated with increased risk of CVD mortality compared with normal BP in the whole cohort. Stage 1 AH was related with increased CVD risk only in those <65 years of age and without a history of CVD, but not in those ≥65 years of age or with a history of CVD . Similar results were obtained in the Chinese Multi‐provincial Cohort Study; the Authors showed that stage 1 AH increased CVD risk in young and middle‐aged Chinese adults, but not in those age ≥60 years .…”
Section: Blood Pressure ≥130/80 MM Hg and Cvd Outcomesupporting
confidence: 70%
“…The Singapore Chinese Health Study that included 30 636 participants revealed that neither elevated BP nor stage 1 AH was associated with increased risk of CVD mortality compared with normal BP in the whole cohort. Stage 1 AH was related with increased CVD risk only in those <65 years of age and without a history of CVD, but not in those ≥65 years of age or with a history of CVD . Similar results were obtained in the Chinese Multi‐provincial Cohort Study; the Authors showed that stage 1 AH increased CVD risk in young and middle‐aged Chinese adults, but not in those age ≥60 years .…”
Section: Blood Pressure ≥130/80 MM Hg and Cvd Outcomesupporting
confidence: 70%
“…Many countries in Europe or Asia have carefully considered whether the new guideline is suitable for localization across the difference of geographical regions and ethnicities [13][14][15]. A data from the Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA)/Cooperative Health Research in the Region of Augsburg (KORA) cohort study involving 11,603 subjects showed that stage 1 hypertension did not increase the risk of cardiovascular disease (CVD) mortality compared with normal BP [13].…”
Section: Introductionmentioning
confidence: 99%
“…A data from the Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA)/Cooperative Health Research in the Region of Augsburg (KORA) cohort study involving 11,603 subjects showed that stage 1 hypertension did not increase the risk of cardiovascular disease (CVD) mortality compared with normal BP [13]. Similarly, another study demonstrated that the newly defined stage 1 hypertension was not associated with increased risk of CVD mortality among Chinese in Singapore aged 46-85 years [14]. In contrast, stronger associations with subsequent CVD events were observed in those with baseline stage 1 hypertension among Korean young adults [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi Y et al demonstrated that stage 1 hypertension increased the risk of cardiovascular events in young and middle‐aged adults, but not in those aged ≥60 years. In addition, Mohammad Talaei, et al indicated that stage 1 hypertension was associated with increased cardiovascular risk only in those <65 years of age and without a history of CVD (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.01‐1.94), excluding those ≥65 years of age or with a history of CVD. These authors also claimed that further validation of their results using a larger sample size of older people is still required.…”
Section: Introductionmentioning
confidence: 99%